Harmonic Mitigated Front End Three Level Diode Clamped High Frequency Link Inverter by Using MCI Technique - Sreedhar Madichetty; Abhijit Dasgupta; Soumyadeep Ray (Institute of Advanced Engineering and Science, 2014)
In this paper it proposes a high efficient soft-switching scheme based on zero-voltage-switching (ZVS) and zero-current-switching(ZCS) principle operated with a simple auxiliary circuit extended range for the front-end isolated DC-AC-DC-AC high power converter with an three phase three level diode clamped multi level inverter by using Minority Charge Carrier inspired optimization technique (MCI) with Total Harmonic Distortion(THD),Switching losses, Selective harmonic elimination maintaining with its fundamental as an objective function. Input to the inverter is obtained by the photo voltaic cells and with battery bank. The switching scheme is optimized by MCI technique, analyzed and executed in Matlab and implemented with a digital signal processor (DSP) .Experimental results with different loads have observed and shows its effectives, robustness of the applied technique.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.5019